Bis(2, 1, 3-benzotelluradiazolidyl)2, 1, 3-benzotelluradiazole: a pair of radical anions coupled by Te⋯N chalcogen bonding. Issue 7 (2nd January 2020) - Puskarevsky, Nikolay A.; Smolentsev, Anton I.; Dmitriev, Alexey A.; Vargas-Baca, Ignacio; Gritsan, Nina P.; Beckmann, Jens; Zibarev, Andrey V.
Abstract : The title species is a trimeric dianion with a singlet ground state, as shown for its [K(18-crown-6)(THF)] + salt. Abstract : Reduction of 2, 1, 3-benzotelluradiazole (3 ) yielded a crystalline solid that features a trimeric dianion formally composed of two [3]˙ − and one 3 bridged by unusually asymmetric Te⋯N chalcogen bonds. The solid is diamagnetic due to strong antiferromagnetic coupling, as revealed by CASSCF/CASPT2 and BS-DFT.